Recurrence of intestinal metaplasia and early neoplasia after endoscopic eradication therapy for Barrett’s esophagus: a systematic review and meta-analysis - Fujii-Lau, Larissa L.; Cinnor, Birtukan; Shaheen, Nicholas; Gaddam, Srinivas; Komanduri, Srinadh; Muthusamy, V. Raman; Das, Ananya; Wilson, Robert; Simon, Violette C.; Kushnir, Vladimir; Mullady, Daniel; Edmundowicz, Steven A.; Early, Dayna S.; Wani, Sachin (Endoscopy International Open, 2017)
Background Conflicting data exist with regard to recurrence rates of intestinal metaplasia (IM) and dysplasia after achieving complete eradication of intestinal metaplasia (CE-IM) in Barrett’s esophagus (BE) patients.Aim (i) To determine the incidence of recurrent IM and dysplasia achieving CE-IM and (ii) to compare recurrence rates between treatment modalities [radiofrequency ablation (RFA) with or without endoscopic mucosal resection (EMR) vs stepwise complete EMR (SRER)].Methods A systematic search was performed for studies reporting on outcomes and estimates of recurrence rates after achieving CE-IM. Pooled incidence [per 100-patient-years (PY)] and risk ratios with 95 %CI were obtained. Heterogeneity was measured using the I2 statistic. Subgroup analyses, decided a priori, were performed to explore heterogeneity in results.Results A total of 39 studies were identified (25-RFA, 13-SRER, and 2 combined). The pooled incidence of any recurrence was 7.5 (95 %CI 6.1 – 9.0)/100 PY with a pooled incidence of IM recurrence rate of 4.8 (95 %CI 3.8 – 5.9)/100 PY, and dysplasia recurrence rate of 2.0 (95 %CI 1.5 – 2.5)/100 PY. Compared to the SRER group, the RFA group had significantly higher overall [8.6 (6.7 – 10.5)/100 PY vs. 5.1 (3.1 – 7)/100 PY, P = 0.01] and IM recurrence rates [5.8 (4.3 – 7.3)/100 PY vs. 3.1 (1.7 – 4)/100 PY, P < 0.01] with no difference in recurrence rates of dysplasia. Significant heterogeneity between studies was identified. The majority of recurrences were amenable to repeat endoscopic eradication therapy (EET).Conclusion The results of this study demonstrate that the incidence rates of overall, IM, and dysplasia recurrence rates post-EET are not inconsiderable and reinforce the importance of close surveillance after achieving CE-IM.